RANCANGAN BUKU AKULTURASI BUDAYA ROTI CAKWE DENGAN PENDEKATAN FOTOGRAFI - Junior, Edbert Andy; Erlyana, Yana (Desain Komunikasi Visual, Manajemen Desain dan Periklanan (Demandia), 2023)
Indonesia is well-known for its cuisine, which is a result of cultural acculturation. However, the rapid and increasingly varied development of culinary innovations has caused the existence of traditional foods to be increasingly displaced and threatened with extinction. By making this work, the goal is to increase awareness of one of the local traditional foods, cakwe bread, by showing the historical, social, and cultural value of traditional Indonesian food. The research uses the design thinking method in designing a photography book with an emotional, creative, and artistic approach. The research results show that the use of photography in the design of this book has an important role in helping to convey the information. This design is hoped to increase the younger generation's awareness about preserving traditional cuisine in Indonesia.Keywords: Photography, acculturation, Culinary, design thinking